The influence of the natural environment on learning in primary school students - Marina Duset Panareda (Journal of Neuroeducation, 2021)
Contact with nature changes us in many ways: after a walk in the forest, our body, brain and feelings are different. Those changes have an explanation: green places provide us with numerous benefits. This scientific review explores the relationship between nature and primary education, and the results can make a difference in the way we teach and how we can rethink the education locations. For that, we use the research of the last years to know the scientific evidence that nature produces in students. First, you can find a comparison between rural and urban areas as a place of living and studying and the decreasing numbers of people living in the countryside, compared with the increasing amount of the population moving into the urban areas. Moreover, in this article, you can find how nature can stimulate the brain in a way that provides benefits for academic tasks and also helping students having better behaviour and health. Furthermore, knowing which kind of places provides a better function of learning is a part that the article reports and relates to green spaces. Decreasing levels of cortisol, higher levels of concentration, motivation or more participation of the students, are some of the results that you can find when nature surrounds you. Though, it is not all about benefits for education, but also health takes part when it mixes with nature: we can find fewer levels of depression or anxiety. Focusing on building and reconstructing schools providing more green spaces and large windows to observe wildlife can be helpful in a city area. Use the forest or the playground as a place of learning can be another easy and effective way of taking all the benefits that nature can provide to our students in rural areas.